Global Models Must Meet Grassroots Action to Deliver Climate Solutions for Farmers - Challinor, Andrew J.; Vermeulen, Sonja J. (2016)
This is the third article of the UNAI ‘Food Security and Climate Change’ series. Schools and departments which specialise in climate change and food security at UNAI member institutions were asked to submit articles highlighting research and work encompassing the newly adopted Sustainable Development Goals and to showcase the importance of sustainable agriculture to mitigate the dangerous effects of climate change, whilst ensuring present and future food security. Please note that the articles are for discussion, and do not necessarily reflect the views of the United Nations.